Blaze and the Lost Quarry - Anderson, C. W.; Nang Chan Yeema (New York, USA Aladding Paperbacks, 2000)
Billy and his pony Blaze discover the way to an abandoned quarry where they perform a brave deed.
Keywords: Story Collection